AN INVESTIGATION INTO STYLISTIC DEVICES IN SONGS BY THE BEATLES - Hoàng Thị Huyền Nhi (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis examined stylistic devices frequently used in songs by the Beatles.The data of the study were collected from some famous websites on the internet.The data were described and analyzed in the qualitative and quantitative approaches to yield more precise points on stylistics in songs by the Beatles. On a close analysis, the thesis made attempts to find out some commomly used stylistic devices the Beatles’songs namely metaphor, simile, repetition, rhyme, alliteration and parallelism and to find out the combination of stylistic devices in songs, some pedagogical implications and some main findings include with a hope of contributing to better teaching and learning English as a foreign language, especifically to better familiarizing learners in understanding and writing a beautiful and interesting songs.